Dari Pinggiran ke Pusaran Revolusi: Sejarah Sehari-hari dan Transformasi Sosial di Suliki, 1945-1949 - Safitri, Novrila (Jurnal Ceteris Paribus, 2025)
This article examines the dynamics of the Indonesian National Revolution (1945-1949) from a micro-perspective, focusing on the everyday historical experiences of the community in the Suliki District, West Sumatra. Utilizing historical methods that rely on archival primary sources and, in particular, in-depth interviews with historical actors and witnesses, this research reconstructs how a remote hinterland was abruptly transformed into an epicenter of the struggle after being chosen as the base for the Emergency Government of the Republic of Indonesia (PDRI) in 1948. The findings reveal that the revolution in Suliki was not merely understood as a military event, but more profoundly as a process of deep social transformation. Community support was expressed through daily practices, including logistics provision, housing, work in public kitchens, and participation in local resistance forces (BPNK). The solidarity forged between PDRI officials and local residents created an intimate support ecosystem, blurring the lines between the war front and domestic life. This study concludes that social networks and the agency of grassroots communities at the local level were crucial in underpinning the resilience of the Republic during the emergency period. It offers the perspective that the revolutionary center of gravity could shift and be found within the small-scale narratives of areas considered peripheral.